Relationship Between Intestinal Parasitic Infection and Anemia in School-Going Girls: A Cross-Sectional Study - Sirichand, Adnan Bashir, Farhan Saeed, Taj Muhammad Laghari, Amanullah Lail, Nadia Nahal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The purpose of this study was to determine the prevalence of anemia and intestinal parasite infection in school-going adolescent girls. Study design: A cross-sectional study Place and Duration: This study was conducted at Hamdard University of Medicine and Dentistry Karachi from march 2021 to march 2022. Methodology: There were eight schools in the research area, and three were chosen at random. Each school used universal sampling, and 250 voluntarily participating girls were included in the study. A sample of the morning's stool was taken for microscopic analysis, and hemoglobin levels were calculated. Relevant data were gathered using a structured questionnaire that had been evaluated beforehand, and SPSS version 22 was used for data analysis. Results: The most often isolated organism is Entamoeba histolytica, which is followed by Giardia intestinalis (5.2%), hookworm (4.4%), and Ascaris Lumbricoides (3.2%). A total of 36% of patients had intestinal parasite infection, according to the research. Mild, moderate, and severe anemia were found to be present in them at rates of 12.8%, 46.8%, and 25.2%, respectively, with a prevalence of anemia of 84.8%. Anemia, insufficient hand washing techniques, and intestinal parasite infection were all found to be statistically significantly correlated. Practical implication: We can minimize the likelihood of acquiring iron deficiency anaemia, which would increase the morbidity of school-going girls and increase their vulnerability to malnutrition and poor academic performance, by detecting worm infestation early on through routine screening tests. Conclusion: According to the study, female school-going children had a significant prevalence of anemia and intestinal parasite infection. Preventive interventions, such as regular deworming and health education about eating a diet that is nutritionally balanced, taking iron supplements, and practicing good personal hygiene, are required for parents and their children in order to avoid and minimize the burden of disease. Keywords: Anemia, Worms infestations, school-going girls, iron supplements